Potentiality of poetic thought: J. H. Prynne’s Sub Songs - Pietrzak, Wit (Studia Anglica Posnaniensia, 2023)
The present article explores J. H. Prynne’s 2010 collection Sub Songs and its employment of what Prynne terms poetic thought, a capacity of language to contest its own reification in the process of permanent contradiction within lexis. Setting Sub Songs against the context of Prynne’s other writings, both poetical and critical, the essay argues that the poems in the volume set out to challenge received modes of thinking about truth and freedom. This is done through what is here termed directed potentiality, understood as these poetic texts’ evocation of shifting constellations of possible meanings, whose openness, however, is directed at critically evoking certain problematic aspects of the world through such means as the repetition of lexical items as well as intertextual and sonic allusiveness. It is by using this technique that Sub Songs critiques mendacious linguistic practices, which inform the crises of interpersonal commitment and intellectual stupor that the world as evoked in Sub Songs is fraught with.